Application of Bioameliorant and Biofertilizers to Increase the Soil Health and Rice Productivity - Tualar Simarmata; . Hersanti; Tien Turmuktini; Betty N. Fitriatin; Mieke R. Setiawati; . Purwanto (Bogor Agricultural University, Indonesia, 2016)
The major rice intensity of diseases in Indonesia was increased significantly and has caused a yield loss of up to 20–30%. The experiments had been conducted to investigate the effect of bioameliorant or composted straw (CS) combined with consortia of biofertilizers (CB) and biocontrol agent to restore the soil health and promote the induced systemic resistance (ISR) for increasing the rice productivity. The experiment arranged as randomized block design consisted of 12 treatments (0, 2.5, 5.0 and 7.5 ton of CS per ha combined with 400 g of CB and 200 g inoculant of CB + 200 g inoculant of Trichoderma sp and was provided with three replications. The experimental results revealed that application of 2.5–7.5 ton per ha of bioameliorant combined with 400 g per ha of CB and 400 g Trichoderma sp has increased the ISR and enhanced the rice productivity significantly. The brown spot, sheath rice blightand bacterial leaf blight diseases were reduced from 16.7% to 3.3–8.0%, 20% to 4–10%, 24% to 2.7–4.7% and 20.7% to 8–14.0%, respectively at 7 weeks after transplanting. In addition, the rice grain yield was increased from about 7.1 ton ha−1 to 7.9–10.1 ton per ha.